DEDIKASI MAHASISWA KKN TEMATIK EKOTEOLOGI DAN PERTANAHAN: PENGABDIAN KEPADA MASYARAKAT DI DESA KARANGDADAP KABUPATEN PEKALONGAN - Fauzia Nur Aeni; Inka Aruri; Vanessa Imeldalia; Nadia Salsa Nabila; Arifiani Ayu Budiati; Zahrotul Aini; Siti Nur Kholipah; Nurul Zahroya; Rheisa Nailatul Izza; Hanif Ithisam Wibowo; Ikhlasa Akmal Fajar; Mukhammad Risqy; Muhlisin (STAI Nusantara Kota Banda Aceh, 2025)
The focus and purpose of this research is about the KKN Ecotheology and Land activities, where this activity is carried out to identify and provide solutions to problems in Karangdadap Village. One of the focuses of the KKN activities of group 13 of the K.H. Abdurrahman Wahid Pekalongan State Islamic University is to carry out socialization related to waste sorting to women's groups, socialization and implementation of waste banks in junior high schools, socialization of making aromatherapy candles from used cooking oil, socialization of biopores, socialization of anti-bullying in MIS Karangdadap and SDN Karangdadap, socialization of waste sorting and making trash cans from used gallons in SDN Karangdadap, additional teaching at MIS Karangdadap, teaching at Paud Menur and handling the problem of uncertified waqf land. The method used is a qualitative descriptive method through observation, surveys and activity planning and documentation as data collection techniques carried out in Karangdadap Village, Karangdadap District, Pekalongan Regency. The results of this study indicate that the Thematic Community Service Program (KKN) in Ecotheology and Land Management increased community awareness and participation in environmental management, supported improvements in educational quality, and identified issues related to uncertified waqf land in Karangdadap Village.